Overproduction and Characterization of Recombinant Soluble Trypanosoma brucei Phospholipase A2 - Oluwafemi Abiodun Adepoju; Daniel Quinnell; Harshverdhan Sirohi; Emmanuel Amlabu; Abdullahi Balarabe Sallau; Abdulrazak Ibrahim; Sunday Ene‐Ojo Atawodi; Mohammed Nasiru Shuaibu; Geoffrey Chang; Emmanuel Oluwadare Balogun (Engineering in Life Sciences)
ABSTRACT Trypanosoma brucei phospholipase A2 (TbPLA2) is a validated drug target but the difficulty in expressing its soluble recombinant protein has limited its exploitation for drug and vaccine development for African and American trypanosomiases. We utilized recombinant deoxyribonucleic acid (DNA) technology approaches to express soluble TbPLA2 in Escherichia coli and Pichia pastoris and biochemically characterize the purified enzyme. Full‐length TbPLA2 was insoluble and deposited as inclusion bodies when expressed in E. coli. However, soluble and active forms were obtained when both the full‐length and truncated TbPLA2 were expressed in fusion with N‐terminal FLAG tag and C‐terminal eGFP in P. pastoris, and the truncated protein in fusion with N‐terminal FLAG tag and C‐terminal mClover in E. coli. Truncated TbPLA2 lacking the signal peptide and transmembrane domain was finally expressed in Rosetta 2 cells and purified to homogeneity. Its migration on sodium dodecyl polyacrylamide gel electrophoresis (SDS‐PAGE) confirmed its size to be 39 kDa. Kinetic studies revealed that the enzyme has a specific activity of 107.14 µmol/min/mg, a Vmax of 25.1 µmol/min, and a KM of 1.58 mM. This is the first report on the successful expression of soluble and active recombinant TbPLA2, which will facilitate the discovery of its specific inhibitors for the development of therapeutics for trypanosomiasis.